Pengaruh Komunikasi Kepemimpinan, Komunikasi Internal, dan Komunikasi Digital terhadap Work Engagement: Peran Moderasi Organizational Trust - Serius Zebua (eCo-Fin, 2025)
This study investigates the influence of leadership communication, internal communication, and digital communication on employee work engagement, with organizational trust as a moderating variable. Using an explanatory quantitative approach, data were collected through structured questionnaires distributed to 150 permanent employees in service-sector organizations within Greater Jakarta that utilize digital communication systems. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Results show that internal and leadership communication significantly enhance work engagement, whereas digital communication does not exhibit a significant effect. Organizational trust does not have a direct impact on work engagement but plays a moderating role in strengthening the effects of leadership and digital communication. The overall predictive power of the model is weak, with low R² (0.024) and Q² (0.004) values, and effect sizes (f²) below the threshold of practical relevance. These findings highlight the contextual nature of communication effectiveness and suggest that organizational strategies should focus on improving interpersonal communication and cultivating trust as an enhancer of communication outcomes. The study contributes to the literature by offering a comprehensive model that integrates multiple dimensions of communication and explores the conditional effects of trust in the digital era.